EKSISTENSI TARI PERSEMBAHAN MAKAN SIRIH DI SMP KELURAHAN BULIANG KECAMATAN BATU AJI BATAM - Reni Nadia Fetrin; Zora Iriani; Darmawati Darmawati (SENDRATASIK UNP, 2018)
Abstract This research aims to disclose and describe the existence of the Makan Sirih  Offerings dance Neighborhood Junior High School in Buliang sub district of Batu Aji Batam.This type of research is qualitative research with a descriptive method. The object of this research is the Makan Sirih Offerings dance Neighborhood Junior High School in Buliang sub district of Batu Aji Batam. The main instrument in this study the researcher himself, and assisted with the instruments supporting such as stationery, photo camera, handy-cam, cassette cd and pendrive. The type of data in this study is the primary data and secondary data. The techniques used in the collection of this data is the study of librarianship, observation, interview and documentation. Technique of data analysis was done with the steps, carrying out data display data or presentation of data, taking the conclusion/verification.The results showed that the Makan Sirih  Offerings dance indeed existed in the Buliang Sub-district (kecamatan) Junior High School Batu Aji. The existence of the Makan Sirih Offerings dance Neighborhood Junior High School in Buliang sub-district of Aji Stone Batam survive from the early use of Buliang Village sub district Junior High School in Batu Aji so that it is now in the midst of people have started to become a culture for community Subdistricts of Buliang and can be accepted and recognized by the society of the village Buliang on the present. Keywords: Existence, Makan Sirih  Offerings dance